(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder with a complex symptomatology, and core symptoms as well as functional impairment often persist into adulthood. Objectives: The Purpose of present study is to motivate other researchers to conduct a study on yoga and its impact on people suffering with AttentionDeficit Hyperactivity Disorder and spread knowledge about yoga and it’s benefits on neurodevelopmental disorders like ADHD, Attention-Deficit Disorder (ADD), and Autism Spectrum Disorder (ASD). Method: This article was compiled through previous studies which are available on the internet, in theses, and in books. Search through Electronic database to identify all related articles on Yoga and its impact or effect on the children suffering with ADHD.